Legal Security Regarding Labels and Certification of Halal Food Products Based on Law Number 33 of 2014 Concerning the Assuredness of Halal Products - Slamet Pribadi; Fitriana, Diana (Dinasti Research, 2022)
Concerning the food consumed, there are factors that influence the decision to consume the food. Sometimes, in choosing food, taste is the main factor that drives this consumption behavior; on the other hand, it can be less concerned with the halal aspect. Muslim consumers guided by Islamic law should pay close attention to the halal aspect of the product and hope that every product they consume fulfills the halal criteria. Paying attention to the MUI halal label on food product packaging is one way to determine whether a product is safe and halal. But unfortunately, not all people are equipped with knowledge about the halalness of a product to gain the benefit and pleasure of Allah SWT. The purpose of this is to do this considering that not all Muslims understand that what they consume is not halal according to sharia law. Besides that, it is also necessary to provide understanding, affirmation, and knowledge to producers to protect the rights of Muslim consumers. As a country with the largest number of Muslims in the world, producers should be more concerned with achieving the safety and comfort of Muslim consumers. The most important thing for producers to know is that halal certification and labeling are not only for the safety of Muslim consumers but also provide economic benefits for producers.